CT: Centro Tecnológico - Rodrigues Pereira, Marcos Calebe; Giacon Villani, Luis Gustavo; Sancio, Karla; Costa, Patrícia D.; Gomes, Roberta; Demonel Lima, Wander; Souza Kubit, Jessica; Figueiredo Gonçalves, Iris; Teixeira da Silva, Marissa; Kumm Tavares, Emilly; Fragoso Dias, João Victor; E. Silva Souza , Vítor; et al. (Guará Journal, 2023)
Resumos dos projetos do Centro Tecnológico.